A Brief Study on Whether Media Enhance or Prevent Panic During Disasters - Dabas, Pooja (Integrated Journal for Research in Arts and Humanities, 2022)
This study examines the role of media in either enhancing or preventing panic during disaster situations, focusing on how various media practices influence public perception and behavior. Through a mixed-methods approach that includes content analysis, surveys, and interviews, the research identifies key factors that shape the media's impact, including tone, source credibility, message framing, and visual presentation. Findings reveal that responsible media coverage—characterized by a calming tone, credible sources, and constructive messaging—can reduce public anxiety, fostering rational and cooperative responses. Conversely, sensationalism, emotional language, and graphic visuals are shown to amplify fear, leading to behaviors associated with panic, such as hoarding and social withdrawal. This study underscores the ethical responsibility of media to avoid sensationalism and prioritize accurate, balanced reporting during crises, ultimately highlighting the media’s potential to promote public resilience and support effective crisis management. These insights contribute to the ongoing discourse on media ethics, disaster communication, and the role of journalism in shaping public welfare during emergencies.